Grief, Emotional Communities and Anglo-French Rivalry in Late-Medieval English and French Literature - O'Connell, Julia Roisin (Trinity College Dublin. School of English. Discipline of English, 2021)
This thesis provides the first extended study of the representation of grief in late-medieval English and French literature. It examines a range of medieval texts, including the Pearl-poem, Geoffrey Chaucer's Book of the Duchess, Charles d'Orléans' Fortunes Stabilnes, Christine de Pizan's Epistre de la prison de vie humaine and Thomas Hoccleve's Series. The thesis explores a range of emotional communities in which grief is expressed in a specific way, through shared emotional vocabularies and distinct emotional regimes. Written in the late fourteenth and early fifteenth centuries, the range of texts included in this study combine the themes of grief and community to respond to the cultural rivalry and military conflict between England and France.
APPROVED
Keywords: Emotional Communities; Literature; Medieval; Middle English; Middle French; Grief